Steroid and steroid regulating hormones in human male castrates - Hampl, R; Zvĕrina, J; Sulcová, J; Stárka, L (Experimental and clinical endocrinology, 1988)
Testosterone, dihydrotestosterone, androstenedione, dehydroepiandrosterone and its sulphate, 11 beta-hydroxyandrostenedione, 17 alpha-hydroxyprogesterone, cortisol, LH, FSH and sex hormone binding globulin (SHBG) were determined in 16 otherwise healthy male castrates, orchidectomized for the forensic reasons. Their hormone levels were compared with those, obtained in normal males of the same age category. There were found in the castrates decreased levels of testosterone, dihydrotestosterone, dehydroepiandrosterone sulphate and androstenedione, unaltered concentrations of cortisol and dehydroepiandrosterone, whereas the levels of 11 beta-hydroxyandrostenedione, 17 alpha-hydroxyprogesterone, both gonadotrophins and SHBG were increased. The results point to the importance of the selective increase of the incretory activity of the adrenal cortex in situations, when the gonadal function is impaired or missing.
Keywords: biologické markery; Follicle Stimulating Hormone; globulin vázající pohlavní hormony; folikuly stimulující hormon; Sex Hormone-Binding Globulin; Testosterone; Adult; androgeny; kůra nadledvin; Biomarkers; Androgens; testosteron; hydrokortison; Hydrocortisone; Humans; Luteinizing Hormone; luteinizační hormon; dospělí; Saliva; Adrenal Cortex; mužské pohlaví; Male; Gonadotropins; lidé středního věku; sliny; Orchiectomy; Middle Aged; lidé; gonadotropiny; orchiektomie